2004
DOI: 10.1093/ps/83.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mushroom and herb polysaccharides, as alternatives for an antibiotic, on the cecal microbial ecosystem in broiler chickens

Abstract: An in vivo experiment was conducted to study the potential prebiotic effects of mushroom and herb polysaccharide extracts, Lentinus edodes extract (LenE), Tremella fuciformis extract, and Astragalus membranaceus Radix extract, on chicken growth and the cecal microbial ecosystem, as compared with the antibiotic Apramycin (APR). This investigation was carried out in terms of a dose-response study. The chickens were naturally infected with avian Mycoplasma gallisepticum prior to the experiment. The BW gain, cecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
2
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(120 citation statements)
references
References 25 publications
13
94
2
11
Order By: Relevance
“…These herbal plants exert positive effects on growth and health of animals probably by their immuno stimulatory properties (Guo et al, 2004).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…These herbal plants exert positive effects on growth and health of animals probably by their immuno stimulatory properties (Guo et al, 2004).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Different levels of EP extract decreased ileal Coliforms population of quails, but ileal Clostridia population of birds consumed EP extract was not different from control group. Guo et al (2004aGuo et al ( , 2004bGuo et al ( , 2004c found that plants derivatives promoted the growth performance, decreased the populations of coliforms and C. perfringens, and boosted both cellular and humoral immune responses of chickens infected with avian Mycoplasma gallisepticum or Eimeria tenella. Jamroz and Kamel (2002) reported that the dietary plant derivatives diminished Escherichia coli population comparing to the control birds.…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al (2004) obtuvieron resultados equivalentes a los extractos de virginiamicina y hierbas chinas. El uso y efecto de los aceites esenciales, en las dietas para pollos de engorda, han sido documentados en los últimos años (Lee et al, 2003).…”
Section: Resultados Y Discusiónunclassified